2007
DOI: 10.1186/1471-2334-7-81
|View full text |Cite
|
Sign up to set email alerts
|

Poor knowledge – predictor of nonadherence to universal precautions for blood borne pathogens at first level care facilities in Pakistan

Abstract: Background: We conducted an assessment of knowledge about blood borne pathogens (BBP) and use of universal precautions at first level care facilities (FLCF) in two districts of Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 23 publications
(31 reference statements)
10
63
2
5
Order By: Relevance
“…The prevalence of complete hepatitis B vaccination among primary HCWs in rural areas of North West Pakistan was lower than the prevalence among primary HCWs reported from rural Sindh, Pakistan (14) and North India. (17) In a study at first level care facilities in Sindh Pakistan, 50.2% of HCWs (compared with 40.2% in this study), 83% licensed Practitioners (compared with 85.9% in this study), 36.4% non-licensed Practitioners (compared with 27.3% in this study), and 42% Dispensers/assistants (compared with 37.7% in this study) reported complete hepatitis B vaccination.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…The prevalence of complete hepatitis B vaccination among primary HCWs in rural areas of North West Pakistan was lower than the prevalence among primary HCWs reported from rural Sindh, Pakistan (14) and North India. (17) In a study at first level care facilities in Sindh Pakistan, 50.2% of HCWs (compared with 40.2% in this study), 83% licensed Practitioners (compared with 85.9% in this study), 36.4% non-licensed Practitioners (compared with 27.3% in this study), and 42% Dispensers/assistants (compared with 37.7% in this study) reported complete hepatitis B vaccination.…”
Section: Discussionmentioning
confidence: 55%
“…(17) In a study at first level care facilities in Sindh Pakistan, 50.2% of HCWs (compared with 40.2% in this study), 83% licensed Practitioners (compared with 85.9% in this study), 36.4% non-licensed Practitioners (compared with 27.3% in this study), and 42% Dispensers/assistants (compared with 37.7% in this study) reported complete hepatitis B vaccination. (14) A study at a community based hospitals in rural India, reported that 87% HCWs were completely hepatitis B vaccinated. (17) We did not find any other literature about the prevalence of hepatitis B vaccination among primary HCWs from the region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference between allopathic and non-allopathic practitioners in knowledge of PEP regimen for occupational exposure was not statistically significant. Janjua et al 18 concluded that the level of knowledge was a major determinant in adherence to universal precautions at first level care facilities in Pakistan. In a Canadian study, 19 the perception of a physician towards risk of contracting HIV was found to determine his behaviour in preventing an occupational exposure.…”
Section: Post-exposure Prophylaxismentioning
confidence: 99%